The Influence of Channa Striata and Ananas Comosus Floss on Perineal Wound Healing at Aji Batara Agung Dewa Sakti Hospital Samboja - Gloriana, Citra; Hendriani, Dwi; Astuti, Dewi Rinda; Jasmawati (PT FORMOSA CENDEKIA GLOBAL, 2023)
A perineal wound is one of the predisposing factors for puerperal infection. This form of infection varies and is localized, resulting in sepsis and death during the puerperium. One of the risk factors for perineal infection is prolonged perineal wound healing. Channa Striata is one of the fish that contains more nutrients and protein than other types of fish, so consumption of Channa Striata can be used as a type of nutrition to accelerate wound healing. Then in Ananas comosus, you can find a phytochemical content in the form of bromelain, which functions as an anti-inflammatory so that it can prevent wound infection. To determine the effectiveness of Channa Striata and Ananas Comosus shredded on perineal wound healing in postpartum mothers. This research is included in quasi-experimental research with a one-group pretest-posttest design approach. The population is postpartum mothers who experience perineal rupture from either natural injuries or episiotomy wounds at Aji Batara Agung Dewa Sakti Hospital Samboja. The sampling technique uses purposive sampling of as many as 17 people. As a result of the study, this influence exists between Channa Striata and Ananas Comosus Floss in healing perineal wounds (p value = 0.025) with value α = 0.05.Research results show that Channa Striata and Ananas Comosus Floss can help speed up the healing process of perineal wounds. From the research results, Channa Striata and Ananas Comosus shredded can be used as an alternative for perineal wound healing